Emotions as indications to the good: The evaluative function of desire in Aquinas’ ethics - Riedenauer, Markus (Verbum – Analecta Neolatina, 2004)
Aquinas’ ethical theory contains two basic approaches, Aristotelian virtue ethics, and the law. How is their relationship to be understood? Are there genuinely philosophical ethics? We analyse Aquinas’ theories of appetite (§I ) and emotions (§II ), examine their relevance for ethics and their integration into his account of natural law(§III ). Three central formulations give the focus of each part: I. bonum nominat id in quod tendit appetitus - appetitions create motivational relations to the good, the fundamental practical dispositions. II. Passiones appetitus indicatores ad bonum - the emotions are inclinations to the good, thus providing the primary evaluation of situations. Their basic objectivity becomes clearer in Aquinas’ ordering of the passions. III. Secundum ordinem inclinationum naturalium est ordo praeceptorum legis naturae - natural law theory, properly understood, reveals the autonomy of practical reasoning and its independence from metaphysical interpretation exactly because of the theory of desire. The highest praeceptum contains desire insofar as it names the structure of acting as acting which is defined by its relation to something good as good. In my interpretation, neither the virtues nor the law nor the connection of both parts of Aquinas’ ethical theory can be understood without desire, passiones, appetitus naturalis.